2022
DOI: 10.3390/molecules27030767
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Molecular Docking, and Evaluation Antioxidant and Antimicrobial Activities for Novel 3-Phenylimidazolidin-4-One and 2-Aminothiazol-4-One Derivatives

Abstract: On our way to discovering and developing compounds that have an antioxidant impact compared to ascorbic acid and other biological activities, we designed, synthesized, and evaluated a new series of heterocyclic moieties drugs (1–11) as antioxidants and antimicrobial agents. As starting moieties, these new candidates were derived from two promising heterocyclic compounds, imidazoldin-4-one and thiazol-4-one. Firstly, diphenylimidazol 1 was obtained because of the cyclo condensation one-pot ternary reaction of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The modeling was done using Molecular Operating Environment (MOE-2015) software, which offers a unique set of capabilities for modeling protein/ligand interactions. [32,33] The X-ray crystallographic structure of the VEGFR-2 enzyme (PDB ID: 1YWN) was downloaded from the protein data bank. [34,35] Water molecules and ligands not involved in the interaction were removed from the co-crystallized enzyme.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…The modeling was done using Molecular Operating Environment (MOE-2015) software, which offers a unique set of capabilities for modeling protein/ligand interactions. [32,33] The X-ray crystallographic structure of the VEGFR-2 enzyme (PDB ID: 1YWN) was downloaded from the protein data bank. [34,35] Water molecules and ligands not involved in the interaction were removed from the co-crystallized enzyme.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…56 Consequently, it will be possible to recognize which specic structural modications are required to achieve outstanding efficiency in a simple and low-cost way. [57][58][59][60] Fortunately, our candidates exhibited signicant antiinammatory inhibitory activity. These candidates also exhibited considerable antioxidant activity compared to ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%
“…A crystal structure of cytochrome c peroxidase enzyme that previously co-crystalized with ascorbic acid was obtained from the protein data bank (PDB code: 2X08). This enzyme-ligand complex was used before for modelling the 3-phenylimidazolidin-4-one and 2-aminothiazol-4-one derivatives against ascorbic acid as a reference ligand [37]. Molecular docking revealed that these compounds are embedded deeply into the binding pocket of cytochrome c peroxidase to interact with vital hydrophilic residues (Fig.…”
Section: Biological Evaluationmentioning
confidence: 99%